Recombinant guanosine-5′-triphosphate (GTP)-binding protein associated with Poloxamer 407-based polymeric micelles protects against Leishmania infantum infection. (May 2022) - Lage, Daniela P.; Machado, Amanda S.; Vale, Danniele L.; Freitas, Camila S.; Linhares, Flávia P.; Cardoso, Jamille M.O.; Pereira, Isabela A.G.; Ramos, Fernanda F.; Tavares, Grasiele S.V.; Ludolf, Fernanda; Oliveira-da-Silva, João A.; Bandeira, Raquel S.; et al.
Graphical abstract: Highlights: A GTP-binding protein was used as recombinant antigen against L. infantum . It was associated with saponin or in polymeric micelles as adjuvants. Results showed that rGTP/Sap and rGTP/Mic induced the Th1-type immune response. Immunized mice showed also higher lymphoproliferation and lower parasitism. The rGTP/Mic composition was more immunogenic and protective than rGTP/Sap. Abstract: Leishmania virulence proteins should be considered as vaccine candidates against disease, since they are involved in developing infection in mammalian hosts. In a previous study, a Leishmania guanosine-5′-triphosphate (GTP)-binding protein was identified as a potential parasite virulence factor. In the present work, the gene encoding GTP was cloned and the recombinant protein (rGTP) was evaluated as a vaccine candidate against Leishmania infantum infection. The protein was associated with saponin (rGTP/Sap) or Poloxamer 407-based micelles (rGTP/Mic) as adjuvants, and protective efficacy was investigated in BALB/c mice after parasite challenge. Both rGTP/Sap and rGTP/Mic compositions induced a Th1-type immune response in vaccinated animals, with significantly higher levels of IFN-γ, IL-12, IL-2, TNF-α, GM-CSF, nitrite, specific IgG2a isotype antibody and positive lymphoproliferation, when compared to the control groups. This response was accompanied by significantly lower parasite load in the spleens, livers, bone marrows and draining lymph nodes of the animals. Immunological and parasitological evaluations indicated that rGTP/Mic induced a more polarized Th1-type response and higher reduction in the organ parasitism, and with lower hepatotoxicity, when compared to the use of rGTP/Sap. In conclusion, our preliminary data suggest that rGTP could be considered for further development as a vaccine candidate to protect against VL.